EFEKTIVITAS MODEL PEMBELAJARAN NUMBERED HEAD TOGETHER (NHT) TERHADAP HASIL BELAJAR MATEMATIKA SEKOLAH DASAR - Agung Sapto Nugroho; Nyoto Harjono (Universitas Borneo Tarakan, 2020)
Abstract: The purpose of this research was to re-analyze the use of cooperative learning type numbered head together model in increasing the learning outcome in mathematics studies subject. The research method was meta-analysis. The research began with formulating research problems, then trancing relevant research result to be analyzed. The data was collected by browsing article, electronic journals, and essay using “learning outcomes”, “numbered head together model”, and “Mathematics Studies of Primary Education”. The searching result showed that there were 13 articles, electronic journals, and essay but only 9 relevant articles, electronic journals, and essay. The data were analyzed using qualitative descriptive analysis. The analysis result showed that cooperative learning type numbered head together model could improve student’s learning from the lowest 15,81%. to the highest 91,88% and the mean was 43,85%.Abstrak: Tujuan dari penelitian ini adalah untuk menganalisis kembali penggunaan model pembelajaran tipe kooperatif tipe numbered head together dalam menaikkan hasil belajar pada mata pelajaran Matematika. Metode penelitian adalah meta-analisis. Penelitian dimulai dengan merumuskan masalah penelitian, kemudian menguji hasil penelitian yang relevan untuk dianalisis. Data dikumpulkan dengan menelusuri artikel, jurnal elektronik, dan esai menggunakan